Methodologies for evaluation of high strain rate properties of composite material constituents - Chacko Salem, Stanley (2016)
Virtual testing using high strain rate material data can play a major role in realising an optimum design of composite parts for impact and crash resistance. The objective of this thesis was to develop methodologies for generation of high strain rate properties of composite material constituents and demonstrate their use with an already developed multi-scale modelling platform [1] for prediction of the probabilistic strength of composite materials. Two different approaches were used for generation of the high strain rate data of the fibres and resins. The first one is the direct evaluation of properties through experimental testing and the other is an inverse modelling approach which uses the test data of composites to provide information on the constituent data, using the micro-scale models [1], through an iterative optimisation study. A split Hopkinson tensile bar was developed with an innovative clamping methodology which was used to generate the high strain rate tensile characteristics of carbon fibres. An inverse modelling methodology was used in conjunction with the high strain rate data from the longitudinal and transverse compression of unidirectional composites to generate the longitudinal and transverse compressive properties of the fibre. The constituent’s data generated was then further used in the multi-scale model for probabilistic prediction of respective composite strength through Monte Carlo simulations. This study was primarily focussed on generating data for carbon fibre composites. The contribution to knowledge from this study is the demonstration of the use of hybrid approach of generation of data in conjunction with multi-scale models for prediction of the strength properties of composites. This approach can be further applied for different multi-scale models relating to different composite architecture for evolution of new optimum designs for impact and crashworthy applications. Specific areas of novelty related to this thesis can be summarised as follows: 1) Development of an innovative clamping methodology for high strain rate tensile testing of fibres. 2) Development of an inverse modelling approach for generation of longitudinal and transverse compressive properties of fibres. 3) Use of analytical Jacobian for improved efficiency during optimisation for inverse modelling studies 4) Generation of high strain rate data of standard carbon fibres such as T800, T700 and IM7.